Bosnia and Herzegovina : Request for Stand-By Arrangement; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses the request from the Bosnia and Herzegovina authorities for a Stand-By Arrangement. The global financial and economic crisis hit Bosnia and Herzegovina when the overheating was already raising doubts about the sustainability of the economic expansion. The authorities' comprehensive financial sector strategy aims at strengthening the banking sector and improving crisis preparedness. IMF staff supports the authorities' plans to enhance the monitoring of financial stability by establishing a standing committee in charge of crisis prevention and management, and by signing a formal memorandum of understanding on cooperation.